PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KEBIJAKAN CASH HOLDINGS DENGAN KUALITAS LAPORAN KEUANGAN SEBAGAI MEDIATOR - Nur’aini Rokhmania; Dewi Murdiawati (Universitas Katolik Indonesia Atma Jaya, 2018)
This study aims to examine the effects of corporate governance on cash holding with the quality of financial statements as a mediator. Independent variables used in this study are managerial ownership, institutional ownership, board size, and an independent board of commissioners. The sample used in this research is 100 non-finance companies listed in Indonesia Stock Exchange (BEI) in the period 2014-2016 which is selected by using purposive sampling method. The data were tested using moderated regression analysis (MRA) with SPSS version 20. The results of the test in this study indicate that the quality of financial statements moderate the relationship between the ownership of the institution and the cash holding and the quality of the financial statements moderate the relationship between the independent commissioner and the cash holding, finance does not moderate the relationship between managerial ownership and cash holding and the quality of financial statements moderate the relationship between board size and cash holding.